IMPLEMENTASI ALGORITMA FUZZY C-MEANS PADA PENGELOMPOKAN SISWA PKL: (Studi Kasus: SMK MUTIARA SALAWU) - Uro Abdurohim; Siti Adawiah; Herna Gunawan (LPPM STMIK Bandung, 2020)
Mutiara Salawu Vocational School also participates in government programs for carrying out PKL. However, PKL at SMK Mutiara Salawu is different from other SMKs. While it is not absent, it is rare for SMKs to direct their students to PKL at locations determined based on specific report card criteria. Since SMK Mutiara Salawu places PKL students according to the school's determination, a supportive system is needed to classify students based on the specified report cards. The implementation of the Fuzzy C-Means algorithm is used to classify PKL students based on their respective report cards. The results of this implementation are in the form of software that can be used to help schools classify XI grade PKL students based on report cards, thereby assisting in the preparation of PKL placements according to the preferences of the chosen PKL sites using the Fuzzy C-Means algorithm. Based on the test results, it can be concluded that the grouping of PKL students produces output that meets user expectations.